ORGANIC POLLUTANTS IN THE INDUSTRIAL AREA EAST OF KAVALA, NORTHERN GREECE - Grigoriadou, A.; Georgakopoulos, A.; Schwarzbauer, J.; Kassoli-Fournaraki, A.; Filippidis, A.; Papastergios, G. (Bulletin of the Geological Society of Greece, 2004)
The occurrence and distribution of organic pollutants were studied at in an industrial area situated at the coastal zone east of Kavala, Northeastern Greece. The study focused especially on the area, where the oil facilities of Kavala Oil Co. are located. Three surface water samples were collected and investigated by means of non-target screening analyses to evaluate the level of organic pollution, as well as to reveal molecular markers representing the industrial emissions. The analytical procedure included a sequential extraction of the samples, GC-FID as well as GC/MS analyses (Franke et al., 1995). In the three water samples halogenated compounds, technical additives and synthetic fragrances, phosphates, phthalates, benzothiazoles, esters, ketones, phenols, ethers and PAH's were detected. Quantitative analyses of selected pollutants were additionally performed. Source-specific marker compounds were identified and used to trace different types of emissions throughout the affected environment